Landscape degradation affects red fox (Vulpes vulpes) diet and its ecosystem services in the threatened Ziziphus lotus scrubland habitats of semiarid Spain. (October 2017) - Cancio, Inmaculada; González-Robles, Ana; Bastida, Jesús M.; Isla, Jorge; Manzaneda, Antonio J.; Salido, Teresa; Rey, Pedro J.
Abstract: Habitat loss and landscape degradation affect carnivorous mammal populations and the ecosystem services they provide, but these services are poorly assessed in semi-arid ecosystems. In the Ziziphus semiarid scrublands, a priority habitat for conservation in Europe, we investigated how red fox diet relates to habitat loss and landscape alteration. We further evaluated potential top-down effects of foxes on vegetation through seed dispersal and the control of rabbit herbivory (fruit depulpation interfering seed dispersal). By sampling fox scats, we evaluated the variation in fox diet and its relationship to landscape features and rabbit abundance and activity in 17 habitat remnants distributed throughout the Ziziphus habitat range. Fox diet varied, with diet diversity peaking at intermediate land-use diversity, likely as a consequence of fox's ability to use natural foods and human-derived resources. We confirmed that red fox acts as seed disperser for many species and that it might contribute to control rabbit population and its impact on Ziziphus lotus regeneration by interference on seed dispersal, though this needs experimental corroboration. However, these services were affected by landscape degradation. Our results show that red fox is fundamental for Ziziphus semiarid ecosystem providing key ecosystem services which are presently jeopardized by strong landscape degradation. Highlights: Ecosystem services provided by red fox are examined in protected semiarid habitat. Red fox plays a crucial role for community-level seed dispersal in Ziziphus habitat. Red fox mitigates the impact on seed dispersal of rabbit fruit depulpation. These two fox services have potential to cascade on regeneration of keystone species Ziziphus lotus . Habitat loss and landscape degradation compromise red fox ecosystem services.